2022
DOI: 10.1159/000526577
|View full text |Cite
|
Sign up to set email alerts
|

Factors, Including Clinical Trial Eligibility, Associated with Induction of Third-Line Treatment for Advanced Gastric Cancer

Abstract: Introduction: Third-line chemotherapy has been suggested to improve survival in patients with gastric cancer. This study aimed to identify factors associated with the induction of third-line chemotherapy for advanced gastric cancer, focusing on patient eligibility for clinical trial. Methods: We retrospectively analyzed 335 patients treated for unresectable or recurrent gastric cancer between April 2009 and May 2020. The patients were grouped into those that met the key eligibility criteria for clinical trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A previous database analysis revealed that out of 4522 patients who discontinued second-line therapy, only 2390 (52.9%) received third-line therapy [ 15 ]. Furthermore, other studies have shown that the transition rates from second- to third-line therapy are even lower than those from first- to second-line therapy [ 16 ]. Several complications, including decreased performance status (PS), ascites, and hepatic dysfunction, can preclude the continuation of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A previous database analysis revealed that out of 4522 patients who discontinued second-line therapy, only 2390 (52.9%) received third-line therapy [ 15 ]. Furthermore, other studies have shown that the transition rates from second- to third-line therapy are even lower than those from first- to second-line therapy [ 16 ]. Several complications, including decreased performance status (PS), ascites, and hepatic dysfunction, can preclude the continuation of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%